Fecundidad y comportamiento reproductivo en la sierra y selva del Perú - Fort, Alfredo L. (El Colegio de México A.C., 1992)
The article attempts to discuss the historical and contemporary situations of populations residing in the two least studied areas of Peru: the Andes mountains and the Amazon basin. The study starts with a review of the 'demographic catastrophe’ that the Spanish presence meant to the people of these areas. Hard labour and the spread of new diseases reduced the population sixfold in 30 years, and twenty- three times in a century. The harmful effects of the 'rubber boom' and, more recently, of the 'oil boom', periods are also reviewed.At present, the Amazon area exhibits the highest fertility in the country (6 children per woman), followed closely by the Andes highlands (5.4), both in marked contrast to that of Lima, the capital city (2.5). The rest of the article breaks down this fertility into its three major determinants, marriage, breastfeeding and the use of contraception, following the Bongaarts model, and looks at their relative levels. Such examination reveals a relatively higher level of modern contraceptive use in the Amazon, which is counteracted by an earlier age of union and less breastfeeding than their counterparts in the Andes. These differences are explained in terms of the socio-cultural context prevailing in each setting. Thus, whilst the more liberal attitudes towards sex and modern ideas among the Amazon riverine people are having a net increasing effect on fertility, in the Andes the traditionalist views of their people have kept fertility-inhibiting factors prevalent, such as a relatively later age at marriage and widespread breastfeeding. In the Andes, however, women tend to use more the less effective methods of contraception.Policy implications are derived from these findings and recommendations are put forward for appropriate mch and family planning programmes in these settings.